الدّولة الحماديّة وبنيتها الثّقافيّة - عبود, أوريــدة (Sciences de l'Homme et de la Société, 2017)
تعدّ قلعة بني حماد ثاني دولة تقوم بالمغرب الأوسط بعد دولة الرستميين، وتقع على بعد 20 كلم شمال مدينة المسيلة، وقد أسّسها حماد بن بلكين زيري الصنهاجي الأمازيغي.            تميزت  هذه الدّولة بحركة عمرانيّة نشيطة إبان القرن الحادي عشر (11) واتساعا كبيرا على المستويات الثّقافيّة والعلميّة والاقتصادية، انعكس جليّا باستقطاب شخصيات مشهورة خلال هذه   الفترة عاشت ما يقارب قرنا ونصف.   Abstract : The Bani Hammad Castle is the second country after Morocco East Rustamid state, located 20 km north of liquefied City, was founded by Hammad bin Belkin zairi Senhadji Amazigh.             This marked the state urban movement active during the atheist century (11) and a significant widening of the cultural, scientific and economic levels, reflected clearly attracting famous personalities during this period lived nearly a century and a half.